GAMBARAN FOTO RONTGEN TORAKS PENDERITA HIV/AIDS DAN TB PARU - Mahardika Putra; Waluyo Rudiyanto; Nurul Islamy; M. Ricky Ramadhian (MAJORITY, 2023)
The high morbidity rate caused by infection with the Human Immunodeficiency Virus (HIV) makes many people more susceptible to infection by viruses, fungi or bacteria. One of the co-infections that most often affects people with HIV/AIDS (PLWHA), namely pulmonary TB. based on data from the Lampung provincial health office, the city of Bandar Lampung is ranked first with the number of HIV and pulmonary TB of 1480 cases. Investigations for cases of PLWHA with pulmonary TB are very diverse, one of which is a chest X-ray examination. Chest X-ray examination is known to be easier to find the location of the lesion from tuberculosis and also on the chest X-ray picture usually there are signs that someone has pulmonary TB infection even though there are no symptoms yet. This study used a univariate descriptive research method, the sample of this study was 65 people in RSUD DR. H. ABDUL MOELOEK was taken using the total sampling method. Based on the results of the analysis, the results obtained from 65 samples showed that for the age most people with HIV/AIDS and pulmonary TB were in the age range of 31-40 years as much as 35.4%, then for sex most affected were men as much as 83.1%, based on the shape of the lesion, the most affected were typical lesions 67.7%, for based on the location of the lesion the most patients had lesions in 1 and 2 lobes only in the lung field as much as 27.7%, and for the area of the lesion in HIV/AIDS and pulmonary TB patients the most affected by extensive lesions as much as 40%.